1996
DOI: 10.1021/bi9514471
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Chloride-Depleted Oxygen-Evolving Complex of Photosystem II Studied by Electron Paramagnetic Resonance

Abstract: The effects of different Cl- depletion treatments in photosystem II (PS-II)-enriched membranes have been investigated by electron paramagnetic resonance (EPR) spectroscopy and by measurements of oxygen-evolving activity. The results indicated that the oxygen-evolving complex of PS-II exhibits two distinct Cl(-)-dependent properties. (1) After Cl(-)-free washes at pH 6.3, a reversibly altered distribution of structural states of PS-II was observed, manifested as the appearance of a g = 4 EPR signal from the S2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
63
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 60 publications
(133 reference statements)
7
63
1
1
Order By: Relevance
“…All of these factors affect the hydrogen-bonding network surrounding the OEC, thereby stabilizing one of the two isomers. Also, it has been observed that depletion of Cl -favors the S = 5/2 spin isomer in the S 2 state of spinach PSII (10,11). This observation, however, has not been seen in cyanobacterial PSII indicating that the Cl --binding site and its associated hydrogen-bonding network affects the spin isomer distribution differently in the two species (12).…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors affect the hydrogen-bonding network surrounding the OEC, thereby stabilizing one of the two isomers. Also, it has been observed that depletion of Cl -favors the S = 5/2 spin isomer in the S 2 state of spinach PSII (10,11). This observation, however, has not been seen in cyanobacterial PSII indicating that the Cl --binding site and its associated hydrogen-bonding network affects the spin isomer distribution differently in the two species (12).…”
Section: Introductionmentioning
confidence: 99%
“…Choride is also an essential ion for PSII activity (24,26,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). In plant PSII, removal of Cl Ϫ inhibits oxygen evolution and perturbs the Mn 4 cluster to a variable extent depending on the precise Cl Ϫ -depletion method used (24,26,46).…”
mentioning
confidence: 99%
“…In plant PSII, removal of Cl Ϫ inhibits oxygen evolution and perturbs the Mn 4 cluster to a variable extent depending on the precise Cl Ϫ -depletion method used (24,26,46). The removal of Cl Ϫ by incubation in Cl Ϫ -free buffer increased the proportion of the Mn 4 cluster in the high-spin state (g ϭ 4 EPR signal), but the enzyme continues to work at a reduced rate (46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cofactors serve various functions during water oxidation: The Mn cluster stores at least two of the oxidizing equivalents (namely on transitions S 0 w S 1 and S 1 w S 2 of the catalytic cycle) and may bind the reactive water molecules (5). It is proposed that the cofactor X is both oxidized and deprotonated on S 2 w S 3 (8, 9) and that the two ions adjust the redox potentials of the other compounds (8,13).Tyrosine Y Z probably occupies a position on subunit D1 relative to P 680 which is similar to the one of LArg135 or MHis162 in the reaction center of Rhodopseudomonas Viridis (1,14,15). This has been inferred from the distance estimates of about 12 Å to P 680 (15,(79)(80)(81)) and a projection of about 4 Å on the membrane normal according to the relative electrogenicity of electron transfer between Y Z and P 680 + (16,17).…”
mentioning
confidence: 99%